Journal of Sports Sciences
Contents and summaries of the journal. The Journal of Sports Sciences publishes articles of a high standard on various aspects of the sports sciences covering a number of disciplinary bases, including anatomy, biochemistry, biomechanics, psychology, sociology, as well as ergonomics, kinanthropometry and other interdisciplinary perspectives. In addition to reports of research, review articles and book reviews are published. The emphasis of the Journal is on the human sciences, broadly defined, applied to sport and exercise. Besides experimental work in human responses to exercise, the subjects covered will include technologies such as the design of sports equipment and playing facilities, research in training, selection, performance prediction or modification, and stress reduction or manifestation. Manuscripts dealing with original investigations of exercise, validation of technological innovations in sport or comprehensive reviews of topics relevant to the scientific study of sport will be considered for publication. The Journal presents research findings in the growing area of exercise and sports sciences to an international audience. The readership for this journal is varied and ranges from academic research workers to professionals in recreation, sports coaching and training.